Decrypting the Relationship Between Corruption and Human Development: Evidence from Indonesia - Hardi, Irsan; Saputra, Jumadil; Hadiyani, Rahmilia; Maulana, Ar Razy Ridha; Idroes, Ghalieb Mutig (Ekonomikalia Journal of Economics, 2023)
Corruption is considered endemic in a large part of the world's population and is believed to be a factor that disrupts market behavior and distorts competition, thereby hindering economic growth and human development. This study aims to unveil the impact of corruption on Indonesia's human development through various approaches, utilizing Fully-Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), Moderated Regression Analysis (MRA), Path Analysis, and Vector Error Correction Model (VECM) methods, with data covering the period from 1995 to 2022. The results of the estimation are discussed in three parts: 1) Dynamic Impact, by analyzing the long-term direct effect of corruption on human development; 2) Indirect Impact, by examining the role of government expenditure, tax revenue, and public debt in mediating the effect of corruption on human development; and 3) Causal Impact, by determining the unidirectional and bidirectional relationships between all variables studied. The findings indicate that corruption does not have a lasting direct impact on human development. Moreover, government expenditure and public debt play a role in moderating the impact of corruption on human development. Additionally, there is no causal link between corruption and human development, whereas there are causal connections between human development, government expenditure, tax revenue, and public debt. The results of this study will be valuable in assessing the extent of corruption's impact on human development, particularly in Indonesia, and aim to raise awareness of policymakers, hence encouraging individuals to participate in combating corruption.